Analisis Sistem Cycle Selling Skill Dalam Meningkatkan Penjualan Produk Asuransi Jiwa : (Studi Kasus PT. Prudential Life Assurance Cabang Binjai) - Anni Zuhro Syafrida Hasibuan; Hotbin Husugian; Khairina Tambunan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
In line with increasingly advanced developments and an increasing population, in recent years many conventional insurance companies have offered their newest insurance products, namely life insurance. Life insurance in Indonesia is currently experiencing very rapid growth considering that the majority of Indonesia's population is Muslim. . Therefore, the role of a salesperson or insurance agent really determines the success of a sale, characterized by the salesperson's ability to build good relationships with customers and co-workers. This research uses a qualitative research approach, namely an approach that produces descriptive data in the form of words directly and emphasizes the process rather than the results. The subjects in this research are insurance agents and the object in this research is the Cycle Selling Skill System Analysis in Increasing Sales of Life Insurance Products. The data collection technique in this research uses interview techniques and document study techniques which will be analyzed in presenting the data. The results of this research show that the selling skill system used is still effective and uses the planning, prospect, approach, fact finding, objection, presentation, closing and after-sales service stages. Meanwhile, the obstacles faced were obstacles in planning, prospecting and fact finding.